A systematic review on the use of food web models for addressing the social and economic consequences of fisheries policies and environmental change - Chakravorty, Diya; Armelloni, Enrico Nicola; de la Puente, Santiago (Frontiers in Marine Science, 2024)
Fisheries are complex systems. Food web models are increasingly being used to study the ecological consequences of fisheries policies and environmental change on such systems around the world. Nonetheless, these consequences extend well into the social, economic, cultural, and political domains of such systems. The main goal of this contribution is to characterize how food web models are being used to study the socioeconomic consequences of management actions and environmental change. We conducted a systematic literature review covering research published between January 2010 and July 2023. Only 47 papers (out of an initial pool of 506 publications) met our research criteria. Based on this, it is evident that the body of literature has been increasing slowly and at a constant rate – a condition not shared with other emerging research fields. Modeled systems were mostly marine (87%), covering the waters of 38 countries across 19 Large Marine Ecosystems; albeit mostly in the Global North. The ecological components of the reviewed models (e.g., functional groups) were represented at a much finer scale than their socioeconomic counterparts. Most models were developed using Ecopath with Ecosim (68%) or Atlantis (21%) modeling software suites. Four key research foci were identified across the selected literature. These shaped the methodological approaches followed, as well as the models’ capabilities, the simulation drivers, the way food webs were integrated with bioeconomic models, and the performance metrics they used and reported. Nonetheless, less than half captured social concerns, only one-third addressed trade-offs among management objectives, and only a handful explicitly addressed uncertainty. The implications of these findings are discussed in detail with respect to resource managers needs for ecosystem-based fisheries management and ecosystem-based management. Our collective understanding of the interlinkages between the biophysical and socioeconomic components of aquatic systems is still limited. We hope this review is seen as a call for action and that the food web modeling community rises to the challenge of embracing interdisciplinarity to bridge existing knowledge silos and improve our ability to model aquatic systems across all their domains and components.